Mindfulness-Based Interventions for Professionals Working in End-of-Life Care: A Systematic Review of the Literature. Issue 2 (April 2023) - Covington, Lori; Banerjee, Moitree; Pereira, Antonina; Price, Marie
Objectives: The potential usefulness of mindfulness-based interventions (MBIs) is being investigated for healthcare staff burnout and associated problems, but empirical research on MBI's for end-of-life (EOL) professionals is still in its infancy. The aim of this review is to describe and evaluate the body of evidence-based research on the use of MBIs to support the psychological wellbeing of professional staff in EOL care settings.Methods: A systematic review of the literature was conducted. Database records were extracted from ERIC, PsycInfo, EBSCO, PubMed Central (PMC) and Web of Science, using search terms to locate peer-reviewed studies on professional (not volunteer) staff in dedicated end-of-life settings, administering MBIs not embedded in more general therapeutic modalities (such as ACT or DBT). After removing duplicates, 8701 potential studies were identified: eliminating those that did not fit the eligibility criteria reduced the number of eligible studies to six.Results: A total of six empirical studies were identified and further evaluated. Interventions primarily focussed on reducing burnout symptoms, increasing self-care and self-compassion, and fostering mindfulness. Studies demonstrated very little overlap in treatment, methodology and measures. Only one study was a randomised control trial, which on application of the 3-item Jadad quality scoring, (evidence of randomisation, blinding of researcher to participants' identity and accounts provided of all participants), achieved 1 out of 5 possible points. Furthermore, other concerns were identified as to the study's methodology.Conclusions: Results of this review point to significant gaps in the research on the potential of MBIs to improve the wellbeing of EOL professionals.